Identifying Melodic Motifs and Stable Notes from Gestural Information in Indian Vocal Performances - Shreyas Nadkarni; Preeti Rao; Martin Clayton (Transactions of the International Society for Music Information Retrieval)
Manual gesture plays an important role in Indian classical singing, and one of its functions is to support, illustrate or communicate aspects of raga melody. We explore the relationship between hand movements and melodic elements in Indian classical vocal performances, using kinematic data to classify stable notes and raga-specific phrases. Our findings reveal consistent gestural patterns across singers, with potential applications in gesture-based music analysis.